Prairie restoration project: Alternatives for identifying gifted students. Issue 2 (14th March 2016) - Salisbury, Katie E.; Rule, Audrey C.; Vander Zanden, Sarah M.
Abstract: An authentic, challenging curriculum engaged middle school students from an urban district in exploratory work related to restoring a small prairie at the school. Integrated science-literacy-arts activities were coupled with a system of thinking skills that helped students view issues from different perspectives. Impassioned guest speakers and an enthusiastic teacher inspired students to build a relationship with the content, express their ideas creatively, interact with each other on student-designed projects, and to assume a leadership stance. Middle school students of all academic levels would benefit from teachers implementing similar subject-integrated, real-world-connected work in their classrooms.